Herstellung diastereomerenreiner l- oder u-konfigurierter 1-hydroxybenzylierter Tetrahydroisochinolin-Vorläufer für Aporphin-, Protoberberin-, Quettamin- und Phthalid-Alkaloide (Stereoselektive Synthese von (±)-Ushinsunin und (±)-Oliverolin) - Dieter Seebach; Isabelle M.P. Huber (CHIMIA)
6,7-Dialkoxy-1-bromomagnesio-2-pivaloyl-tetrahydroisoquinolines (THIQ), prepared as previously described for the unsubstituted reagent, are added to bromo-, methoxy-, and ethoxycarbonyl-substituted benzaldehydes to give 1-hydroxybenzylated THIQs of u-configuration exclusively (2a-4a, 5). These are converted to the isomeric pivalates either with retention (u-2b-4b) or with inversion of configuration (l-2b-4b). The diastereomers u-3b and l-3b are hydrolized to the free aminoalcohols (3, R1 = R2 = H) which are N-methylated (→3, R1 = CH3, R2 = H) and cyclized photochemically to the known alkaloids (±)-ushinsunine (u-6) and (±)-oliverolin (l-6), respectively. – The highly functionalized, diastereomerically pure 1-hydroxybenzylated THIQ derivatives described here are versatile precursors for the syntheses of aporphine (see 6), protoberberine, quettamine, and phthalid (see 5) alkaloids.